Предмет: Математика,
автор: tomilova74
-4 (5 - 2m) + 3(m-4) = 6(2-m) - 5m
Помогите решить, в этом ничего не понимаю!(
Ответы
Автор ответа:
1
раскрываем скобки
-20+8m+3m-12=12-6m-5m
-20+8m+3m-12-12+6m+5m
22m-44=0
22m=44
m= 44/22
m=2
-20+8m+3m-12=12-6m-5m
-20+8m+3m-12-12+6m+5m
22m-44=0
22m=44
m= 44/22
m=2
Похожие вопросы
Предмет: Английский язык,
автор: erdlingharty
Предмет: Русский язык,
автор: TimurChik2100
Предмет: Русский язык,
автор: tchernyshova45
Предмет: Математика,
автор: vladcevralov
Предмет: Алгебра,
автор: Ioann2345